Caracterización y evaluación de la contaminación generada por residuos sólidos inorgánicos en los barrancos de la ciudad de Moyobamba - Chong Rojas, Inés (2014)
The ravines of the Moyobamba city, constitute, at the same time, a tourist attraction of the visitors to our city, likewise access that join the city and the ravines are used as viewing-points, from where it is possible to observe the different landscapes that make a detour to the city. Despite the existence of municipal ordinances that resolves that the declared as intangible zones, the population has been used as sites for direct solid wastedisposal. Through this research work was able to determine the ravines that currently are being used for the direct disposal of so lid waste, characterization, as well as the contamination that has been generating. The evaluation was carried out on 09 ravines with presence of solid waste; once identified one proceeded to remove a sample of solid waste and by applying the method of the quartering the calculations as respective volume, density, weight, etc.; the characterization in order to determine the percentages according to its nature; later identified the environmental pollution that has been generating population and the perception of the problem. The results obtained from the 21 ravines identified 09 ofthem equivalent to 42 per cent are used by the population for the solid waste disposal of organic and inorganic directly. A 75.2 per cent are of inorg~nic nature anda 24.8 %are of organic nature.The ravine with the highest percentage of inorganic solid waste are the "market" located between the Jr. Damian Najar and Manuel del Aguila neighborhood of Bethlehem with a 86 %,Tumino located in the Jr. Coronel Bardalez Barrio ofCalvary with 85 %, "Cococho" located in the Jr. San Martin Neighborhood of Saragossa with 78 % followed by other ravines that are below 75 %.According to the characterization conducted the 68.8% is composed of plastics and 16.4 % of paper products, as well as the % of the remaining ( 14.8 ) is composed of glass, iron, and inert material. The pollution is evident, creating conditions for the proliferation of vectors such as (rats, cockroaches, gnats, mosquitoes, etc.), diseases transmitters; on the other hand, the soils desertification, flora loss and fauna macro and microscopic of the area, and on any alteration to their natural beauty. Of the social assessment carried out among the inhabitants located in the nearby areas expressed in a 100% increase in their interest to participare in the care, protection, monitoring of the ravines, for which the 100% believe that mechanisms must be put in organization in order to develop synergies and jointly propose altematives. Key words: solid waste, ravines.